I am falling in love. Ouch!: Ontological metaphors at work - Roselani, Ni Gusti Ayu (Lingua Cultura, 2020)
The research aimed to track the distribution of in metaphors and explore their ontological function in the abstracts of English research articles in the sub-disciplines of theoretical linguistics and pragmatics. The lack of empirical evidence on the subject had become the inspiration to base the research on a corpus. The corpus consisted of 40 research article abstracts; 20 from Journal of Linguistics and another 20 from Journal of Pragmatics. By using a quantitative method, the results show that theoretical linguistics abstracts are more densely populated with ‘in’ metaphors. However, in terms of in-preposition phrase topic complement variations, they are less varied. Qualitatively, the results confirm a notion proposed by Conceptual Metaphor Theory (CMT) that ‘in’ metaphors function cognitively by providing ontological status to abstract objects. Their existence proves to play an important role in academic texts.